THE INFLUENCE OF LEADERSHIP STYLE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Deny Sudrajat; Sugeng Siswondo; Yhonanda Harsono; Otto Fajarianto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study was to determine the effect of leadership style and work discipline on employee performance at PT. Chakra Lestari Sejahtera, both partially and simultaneously. The method used is quantitative descriptive method. The sampling technique used was random sampling using a sample of 52 respondents. Data analysis using validity test, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are the leadership style has a significant effect on employee performance with a correlation coefficient adj value of 0.466 meaning that both variables have a moderate level of influence with a determination coefficient of 46.6%. Hypothesis testing obtained t count> t table or (6.743> 2.009), this is confirmed by a significant probability of 0.000